Percepción de cambio que los pobladores del caserío sol sol se han formado respecto a las estrategias de responsabilidad social aplicadas por sociedad agrícola saturno s.a. durante el periodo 2010 - 2013 - Fernández Herrera, Wendy (2015)
This research was conducted in order to understand the perception of change that the people of Sol Sun has made regarding social responsibility strategies implemented by Saturn SA Agricultural Society between 2010 and 2013. It is a descriptive research character and have used the inductive, deductive, ethnographic and statistical methods, by applying the techniques of observation, interviews and survey. The study was conducted at the Agricultural Society agribusiness company Saturn SA taking as sample universe to 70 heads of household of solsoleña community. During the investigation various questions were covering the social, economic and environmental issues. The responses show that the population is largely satisfied with the actions of social responsibility of business and argue that there have been changes and improvements from the start of operations in the area SAGSA. The areas where the population has seen improvements are social aspects, primarily in the education issue; economic aspect and environmental aspect. Research shows a positive result, it shows that the people of Sun Sun SAGSA perceived as a socially responsible company due to the various actions of social responsibility that has made between 2009 and 2010.